Intervention in acute coronary syndromes: do patients undergo intervention on the basis of their risk characteristics? The Global Registry of Acute Coronary Events (GRACE). Issue 2 (6th June 2006) - Fox, K A A; Anderson, F A; Dabbous, O H; Steg, P G; López-Sendón, J; Van de Werf, F; Budaj, A; Gurfinkel, E P; Goodman, S G; Brieger, D
Abstract : Objective: To determine whether revascularisation is more likely to be performed in higher-risk patients and whether the findings are influenced by hospitals adopting more or less aggressive revascularisation strategies. Methods: GRACE (Global Registry of Acute Coronary Events) is a multinational, observational cohort study. This study involved 24 189 patients enrolled at 73 hospitals with on-site angiographic facilities. Results: Overall, 32.5% of patients with a non-ST elevation acute coronary syndrome (ACS) underwent percutaneous coronary intervention (PCI; 53.7% in ST segment elevation myocardial infarction (STEMI)) and 7.2% underwent coronary artery bypass grafting (CABG; 4.0% in STEMI). The cumulative rate of in-hospital death rose correspondingly with the GRACE risk score (variables: age, Killip class, systolic blood pressure, ST segment deviation, cardiac arrest at admission, serum creatinine, raised cardiac markers, heart rate), from 1.2% in low-risk to 3.3% in medium-risk and 13.0% in high-risk patients (c statistic  =  0.83). PCI procedures were more likely to be performed in low- (40% non-STEMI, 60% STEMI) than medium- (35%, 54%) or high-risk patients (25%, 41%). No such gradient was apparent for patients undergoing CABG. These findings were seen in STEMI and non-ST elevation ACS, in all geographical regions and irrespective of whether hospitals adopted low (4.2−33.7%, n  =  7210 observations), medium (35.7−51.4%, n  =  7913 observations) or high rates (52.6−77.0%, n  =  8942 observations) of intervention. Conclusions: A risk-averse strategy to angiography appears to be widely adopted. Proceeding to PCI relates to referral practice and angiographic findings rather than the patient's risk status. Systematic and accurate risk stratification may allow higher-risk patients to be selected for revascularisation procedures, in contrast to current international practice.